Animal Models to Study Host-Bacteria Interactions Involved in Periodontitis - Graves, Dana T.; Kang, Jun; Andriankaja, Oelisoa; Wada, Keisuke; Rossa, Carlos [UNESP]; Kinane, D. F.; Mombelli, A. (Karger, 2012)
Animal models have distinct advantages because they can mimic cellular complexities that occur in humans in vivo and are often more accurate than in vitro studies that take place on plastic surfaces with limited numbers of cell types present. Furthermore, cause and effect relationships can be established by applying inhibitors or activators or through the use of genetically modified animals. Such gain or loss of function studies are often difficult to achieve in human clinical studies, particularly in obtaining target tissue due to important ethical considerations. Animal models in periodontal disease are particularly important at this point in the development of the scientific basis for understanding the predominant pathological processes. Periodontal disease can be broken down into discrete steps, each of which may be studied separately depending upon the animal model. These steps involve the development of a pathogenic biofilm, invasion of connective tissue by bacteria or their products, induction of a destructive host response in connective tissue and limitation of a repair process that follows tissue breakdown. Animal studies can test hypotheses related to each of these steps, and should be evaluated by their capacity to test a specific hypothesis rather than recapitulating all aspects of periodontal disease. Thus, each of the models described below can be adapted to test discrete components of the pathological process of periodontal disease, but not necessarily all of them. Copyright (C) 2012 S. Karger AG, Basel